2019
DOI: 10.5327/z1679443520190397
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in the context of prevention of absenteeism and presenteeism in the workplace

Abstract: | Background: Oral health is an important factor of human morbidity worldwide. Yet is often neglected in occupational health despite its direct impact on the quality of life and health of workers. Objective: To discuss the role of oral health in sickness absence and presenteeism, as well as in development and work efficiency improvement processes involving governments, companies and the workers themselves. Methods: Review of full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Previous research has shown that workers delay or skip preventive dental examinations because of lack of time or not wanting to burden their co-workers by delegating additional work [ 14 ]. Previous studies have also shown that workers who have more frequent dental visits are more likely to be absent from work [ 23 ]. In addition, many workers do not want to take time away from their jobs, and may therefore stop making preventive dental visits to avoid delaying or not completing work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that workers delay or skip preventive dental examinations because of lack of time or not wanting to burden their co-workers by delegating additional work [ 14 ]. Previous studies have also shown that workers who have more frequent dental visits are more likely to be absent from work [ 23 ]. In addition, many workers do not want to take time away from their jobs, and may therefore stop making preventive dental visits to avoid delaying or not completing work.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of absenteeism from work or school due to dental disease varies in the literature, ranging from 9% in an Australian study to 35.1% in a Canadian study [ 7 , 30 ]. However, many of individuals still go to work and carry out daily activities while experiencing an oral pain episode (presenteeism), which can impair their productivity, promote attention loss, irritability, anxiety, and depression, and increase the risk of work-related accidents [ 5 ]. In the US, almost 321 million hours of work and school are lost per year due to dental problems, of which emergency dental treatment accounted for 92.4 million work or school hours [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature describes the importance of oral health for quality of life, as well as the impact of oral pain on daily activities, especially at work and at school [ 5 7 ]. In addition to causing pain, dental diseases can limit patients’ ability to properly chew, taste, swallow, smile, and find a mate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations